P.A.L.T.: An interdisciplinary model for organizational diagnosis and intervention - Kertész, Roberto; Radano, Eduardo; Velinsone, Daniel; Kertész, Víctor; Landau, Alicia (European Scientific Journal, ESJ, 2017)
In this paper an interdisciplinary and systemic model of organizations of any size is presented, covering four variables: 1. Psychosocial, 2. Administrative, 3. Legal and 4. Technical, under the acronym PALT. We describe their interactions, professional correspondence, the two social systems (family and business) and a classification of small and medium sized businesses according to their maximum annual sales.